SARS-COV-2 infection in a patient with Evans syndrome: a silent enemy or an ally? - Pantić, Nikola M; Mitrović, Mirjana; Virijević, Marijana; Sabljić, Nikica; Pravdić, Zlatko; Suvajdžić, Nada (Vojnosanitetski pregled, 2021)
Introduction. During the current outbreak of Coronavirus disease 2019 (COVID-19), the way to manage patients with autoimmune diseases remains elusive due to limited data available. Case report. We presented a case of a COVID-19 positive 20-year-old female with prior history of Evans syndrome. The patients remained asymptomatic even though she had been treated with immunosuppressants (prednisolone and azathioprine) together with romiplostim. Moreover, her course of infection was accompanied by thrombocytosis, although her platelet count was mostly below the reference range before the infection. The patient was monitored vigilantly, with special regard to platelet count and signs of thrombotic events. Conclusion. Platelet count monitoring and romiplostim administration should be performed more cautiously in chronic immune thrombocytopenic patients infected by SARS-CoV-2.